Adaptive Control of a Hybrid Microgrid With Energy Storage System - Mohamed Ahmed Ebrahim Mohamed; Ali M. El-Rifaie; Bassant Ahmed Bahr; H. E. Keshta; Mahmoud N. Ali; M. M. R. Ahmed (IEEE Open Journal of Power Electronics)
The growing integration of Renewable Energy Resources (RER) and Energy Storage Systems (ESSs) into Hybrid Microgrids (HμGs) downsizes the system inertia that reduces the system ability to maintain the frequency and voltage within the standard levels. To tackle this challenge and enhance the dynamic response of HμGs, PID based model reference adaptive control (MRAC), for the synchronous generator (SG) is applied in this paper. Also, the effect of ESSs on enhancing the system dynamic performance is investigated. The emergence of super capacitor (SC) is suggested to emulate the dynamic inertia response. The SG's adaptive control enables immediate modifications to optimize HμGs frequency, while the rapid response of ESSs stabilizes and supports power generation variations to operate HμGs steadily and overcome the problem of interruptions between load and supply. These combined technologies work together to enhance the dynamic stability of the proposed two-area HμGs system during standalone operation. Advanced metaheuristic optimization techniques are utilized to determine the optimal gains for SC and battery controllers, as well as for MRAC of SG. The obtained results prove the efficacy of the super capacitor and the proposed adaptive control strategy in improving the frequency of HμGs during standalone operation.